The Influence of Dietary Chicken Egg Lysozyme on the Growth Performance, Blood Health, and Resistance Against Escherichia coli in the Growing Rabbits' Cecum - EL-Deep, Mahmoud H.; Amber, Khairy A.; Eid, Yahya Z.; Alrashood, Sara T.; Khan, Haseeb A.; Sakr, Mohamed S.; Dawood, Mahmoud A. O. (Frontiers in Veterinary Science, 2020)
The dietary chicken egg lysozyme (LZM) at different concentrations was tested on the growth performance, blood health, and resistance against Escherichia coli of growing rabbits. A total number of 48 rabbits averaged 611.25 g (five weeks of age) of APRI line-rabbits (Egyptian developed line) were allocated into four treatments (three replicates and each contained four rabbits) of 5-week weaning APRI rabbits. The first group fed basal diet without LZM supplementation and served as a control group. Whereas the remaining groups of rabbits fed a basal diet supplemented with LZM at 50, 100, and 200 mg/kg diet, respectively, for eight weeks. The obtained results revealed that rabbits fed the basal diet supplemented with different concentrations of LZM linearly (P<0.05) displayed improved growth performance and reduced feed intake and FCR. The best result was for rabbits fed diet 200 mg per kg diet supplemented with LZM, followed by 100 mg per kg diet. The total count of Escherichia coli and Clostridium count was linearly (P<0.05) decreased by adding LZM at 100 and 200 mg/kg in the diets compared to the control groups. In contrast, total bacterial count and the total count of Lactobacilli had increased considerably by increasing LZM at different levels relative to the control groups. The LZM supplementation linearly (P<0.05) increased hematological parameters (RBCs, PCV, Hb, and WBCs) together with an increase in lymphocytes count compared to the control group. The total proteins and globulins concentrations were significantly (P<0.05) increased by feeding with LZM. On the other hand, ALT, AST, urea, and creatinine were significantly (P<0.05) decreased by increasing LZM supplementation. It could be concluded that supplementation of the rabbit's diet with chicken egg LZM was able to improve the growth performance, hematological, and serum biochemical parameters compared with the control group. Therefore, LZM is required at the rate of 100-200 mg/kg diet as a potential feed additive, and a friendly alternative for antibiotics in rabbits feed.